2021
DOI: 10.1021/acscatal.1c02171
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Catalytic Sites in Porous Hexagonal Boron Nitride for the Epoxidation of Styrene

Abstract: Porous hexagonal boron nitride (ph-BN) nanosheets were synthesized via the combustion of boric acid and melamine by a pyrolysis method. The as-obtained ph-BN showed a high catalytic activity for the epoxidation of styrene using tert-butyl hydroperoxide as an oxidant. Both experimental and theoretical study demonstrated that the activity originated from the oxygen-containing functional groups at the edges of ph-BN. To further understand the mechanism for this catalytic behavior, in situ Fourier transform infrar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…In an earlier study of the boron-containing ODH catalytic system, we proposed the formation of >B–O–O–B< species at the zigzag edge, which was supported by the recent work of Fu et al that reported the oxidization of >B–OH groups to >B–O–O–B< . Recently Li et al reported boron–oxygen–nitrogen nanotubes (BONNTs) enriched with O–O species exhibited remarkable catalytic activity (a propane conversion of 64.4% with an olefin yield of 48.6% at 525 °C, 2.8 times that on boron nitrogen nanotubes).…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…In an earlier study of the boron-containing ODH catalytic system, we proposed the formation of >B–O–O–B< species at the zigzag edge, which was supported by the recent work of Fu et al that reported the oxidization of >B–OH groups to >B–O–O–B< . Recently Li et al reported boron–oxygen–nitrogen nanotubes (BONNTs) enriched with O–O species exhibited remarkable catalytic activity (a propane conversion of 64.4% with an olefin yield of 48.6% at 525 °C, 2.8 times that on boron nitrogen nanotubes).…”
mentioning
confidence: 60%
“…Figure S4a shows the bond length variation of dioxygen O 13 −O 14 , which increased from 1.214 Å (IM1′) to 1.332 Å (IM2), indicating the activation of the dioxygen molecule. In view of the similar bond length of key chemical bonds in TS2 and IM2, e.g., for O 13 −O 14 (1.305 Å in TS2 vs 1.332 Å in IM2) and for O 13 −H 12 (1.043 Å in TS2 vs 0.993 Å in IM2), TS2 is a late transition state. Furthermore, the free-energy change of TS2 and IM2 is 32.66 and 31.44 kcal/mol, respectively, which is consistent with the Hammond postulate.…”
Section: Peroxo Species At the Zigzag-b Edge (Zigzag-boob)mentioning
confidence: 99%
“…This is the first example of employing LSCF oxides as superior visible‐light catalyst for epoxidation of styrene just using molecular oxygen as the oxidant. Relative with these (7.4∼37.5 mmol ⋅ g cat −1 ⋅ h −1 ) of the reported catalysts coupled with either oxygen or TBHP [6,20,33–36] (Table 1, entries 12–16), LSCF catalyst reported in this work shows the highest reaction rate of ∼50 mmol ⋅ g cat −1 ⋅ h −1 (Table 1, entry 7). Additionally, LSCF catalyst even shows the considerable catalytic performance under visible light compared with the activity of LSCF‐1.6 catalyst under ultraviolet light in our previous study [24] .…”
Section: Resultsmentioning
confidence: 72%
“…Since then, other studies have reported using porous BN or hBN as an intrinsic heterogeneous catalyst or a catalyst support (Table ). , The dominant factor driving catalytic activity is the presence of O-containing groups and more specifically B–OH and B–O–O–B edge groups . For aerobic oxidative desulfurization, zinc (Zn) salt has been used as a template to develop porous BN, and the active site for the oxygen activation is composed of Zn nanoparticles and N-terminated edges …”
Section: Porous Bn For Catalysismentioning
confidence: 99%